Vortex shedding behind an inclined flat plate hinged with a trailing-edge flap - Nonwarit Borvornsareepirom (2020)
© 2019 International Symposium on Turbulence and Shear Flow Phenomena, TSFP. All rights reserved. An influence of a moving motion of a trailing-edge flap on the formation of the wake shed behind an inclined flat plate is investigated via the use of direct numerical simulation (DNS). The leading-edge plate is fixed at an angle of attack of 20°, while its rear part flaps according to a time-dependent equation. The chord based Reynolds number is 1000, while the freestream Mach number is set to 0.4. The movement of the trailing-edge flap alters the formation of the leading-edge and trailing-edge vortices. This leads to the modification of the evolution of the unsteady vortex shedding and the acoustic field, resulting in a reduction in the aerodynamic forces.